2020
DOI: 10.3389/fped.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Hearing Disorders in Asymptomatic Congenital Cytomegalovirus Infection

Abstract: Background and Aim: Cytomegalovirus (CMV) is the main cause of congenital infection in developed countries leading to deafness but the burden of sensorineural hearing loss (SNHL) in asymptomatic children remains incompletely characterized. Aim of this study was to evaluate the long-term audiological outcome in this group of patients.Methods: Consecutive neonates with congenital CMV infection were followed from 2002 to 2018. Patients were considered asymptomatic if free from any clinical and instrumental impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…The diagnosis of cCMV infection in neonates include real-time PCR of saliva, urine or both, as soon as possible after birth within the first 3 weeks of life. Valganciclovir treatment for 6 months in congenitally infected neonates with moderately to severely symptomatic disease could improve audiological and neurodevelopmental outcomes at 2 years of age [ 6 , 7 ]. Early diagnosis of cCMV is mandatory to start therapy within the first month of life.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of cCMV infection in neonates include real-time PCR of saliva, urine or both, as soon as possible after birth within the first 3 weeks of life. Valganciclovir treatment for 6 months in congenitally infected neonates with moderately to severely symptomatic disease could improve audiological and neurodevelopmental outcomes at 2 years of age [ 6 , 7 ]. Early diagnosis of cCMV is mandatory to start therapy within the first month of life.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of cCMV can range from intrauterine growth retardation (IUGR), central nervous system abnormalities like microcephaly, cortical malformations, ventriculomegaly, periventricular calcifications, SNHL, chorioretinitis, hepatosplenomegaly, transaminitis, directhyperbilirubinemia, and petechiae/thrombocytopenia. Isolated SNHL is classified as a subgroup of asymptomatic infection [10]. Infants with SNHL need hearing screening at frequent intervals as SNHL is the most common sequelae of cCMV and 40% of SNHLs are late onset, i.e., after one month of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a population of 92 asymptomatic cCMV children and 51 controls, Lanzieri et al ( 17 ) found that the risk of developing SNHL after age 5 was not significantly different than the risk for uninfected children to develop SNHL, suggesting this hearing loss is likely to manifest before entering grade school. Similarly, Salomè et al ( 21 ) studied the long-term hearing outcomes for 102 children with asymptomatic CMV. After following up with these families for an average of 3.3 years after birth, the researchers did not find a delayed onset hearing loss for any of the children.…”
Section: Discussionmentioning
confidence: 99%